Pembuatan Aplikasi Inventory Barang untuk Promosi di Biro Marketing Universitas Widyatama - Endang Amalia Furkon; Rahmad Prama Yudha (Jurusan Informatika Universitas Jenderal Achmad Yani, 2021)
Widyatama University which is a private university located at Jalan Cikutra Number 204 A Bandung. One of the bureaus found at Widyatama University is the Marketing Bureau. As for the problems that occur in the current system that is for data processing incoming and outgoing goods, reports for incoming goods and reports for outgoing goods, so that sometimes it has difficulty in calculating goods and to get stock information has difficulty sometimes the information provided is not in accordance with the availability of existing goods. The purpose of this research is to make an inventory application of goods for promotion at the Widyatama University Marketing Bureau that can record incoming and outgoing goods, handle the process of making reports on incoming and outgoing goods. This study uses the Prototype method and by using UML (Unified Modeling Language) for structured modeling. The information system that has been produced in this design can manage the data of incoming and outgoing goods, incoming data reports and outgoing data data reports, and making an inventory system of inventory so that the admin can find out the amount of available stock in real time.